Medicinal Chemistry - Vašková, Janka; Vaško, Ladislav (IntechOpen, 2019)
The area covered by this book undoubtedly includes a multidisciplinary approach. It combines and uses the wide range of methods and knowledge from a variety of disciplines in chemistry, pharmacology, and biology to synthesize new or extracted natural substances and their characterization, in terms of bioefficiency in different systems, pharmacokinetics, and pharmacodynamics. Importance is placed on revealing the interactions and effects on organisms. The process is long term, ranging from synthesis to potential testing of substances in animal studies, followed by monitoring effects on patients. The purpose is to define molecular targets of the highest efficacy of the prepared drugs, minimizing the undesirable effects. The content of this book is conceived with these intentions.